Characterization of Mannosyl Dioxanium Ions in Solution Using Chemical Exchange Saturation Transfer NMR Spectroscopy. Issue 6 (27th December 2021) - de Kleijne, Frank F. J.; Elferink, Hidde; Moons, Sam J.; White, Paul B.; Boltje, Thomas J.
Abstract: The stereoselective introduction of the glycosidic bond remains one of the main challenges in carbohydrate synthesis. Characterizing the reactive intermediates of this reaction is key to develop stereoselective glycosylation reactions. Herein we report the characterization of low‐populated, rapidly equilibrating mannosyl dioxanium ions that arise from participation of a C‐3 acyl group using chemical exchange saturation transfer (CEST) NMR spectroscopy. Dioxanium ion structure and equilibration kinetics were measured under relevant glycosylation conditions and highly α‐selective couplings were observed suggesting glycosylation took place via this elusive intermediate. Abstract : Making the invisible visible. Reactive glycosylation intermediates are identified using chemical exchange saturation transfer NMR spectroscopy.